2003
DOI: 10.1080/0962935031000097745
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde in benign prostate hypertrophy: a useful marker?

Abstract: Benign prostate hypertrophy (BPH) is the most common benign tumor in men due to obstruction of the urethra and, finally, uremia. Malondialdehyde (MDA) is a product derived from peroxidation of polyunsaturated fatty acids and related esters. Evaluation of MDA in serum represents a non-invasive biomarker of oxidative stress. Prostate-specific antigen (PSA) is a sensitive marker for prostatic hypertrophy and cancer. We analyzed MDA serum levels to evaluate the oxidative stress in BPH. To this end, 22 BPH patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 5 publications
3
48
0
3
Order By: Relevance
“…Plasma MDA, a key marker of lipid peroxidation, and the most abundant aldehyde generated by the attack of free radicals on polyunsaturated fatty acids of cell membranes, is a non-invasive biomarker of OS in BPH [41,42]. Reductions of plasma MDA with D-004 (32.5%) and SP (28.2%) achieved the efficacy criterion (20.0% decrease versus baseline).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma MDA, a key marker of lipid peroxidation, and the most abundant aldehyde generated by the attack of free radicals on polyunsaturated fatty acids of cell membranes, is a non-invasive biomarker of OS in BPH [41,42]. Reductions of plasma MDA with D-004 (32.5%) and SP (28.2%) achieved the efficacy criterion (20.0% decrease versus baseline).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Pasquale et al 17 demonstrated an association between lipid peroxides and PSA. Although oxidative stress and increase in sialoglycoprotein level and/or sialic acid content are reported in Ca prostate separately; however there are no reports correlating oxidative stress with sialylation parameters in both BPH and Ca prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating MDA levels were found to be significantly higher in BPH patients than in healthy donors [17,[23][24][25] and strongly correlated with prostate-specific antigen levels [23] . However, other works found circulating MDA levels in BPH patients similar to those in controls [26] .…”
Section: Role Of Oxidant Production ( Table 1 )mentioning
confidence: 99%